MENGUKUHKAN POSISI DAN JATI DIRI WANITA EMANSIPASI, GERAKAN DAN REALITAS SOSIAL ISLAM - Ishomuddin, Ishomuddin (Jurnal Bestari, 1994)
In the middle century, the number of seminar was held in some roman churches to discuss the existance of women. The seminar concluded that all women had no soul, and they differed form women are men's partness. Women and men should make  a harmonious family and make their dream come true.